2014
DOI: 10.1103/physrevb.90.024515
|View full text |Cite
|
Sign up to set email alerts
|

Limiting mechanism for critical current in topologically frustrated Josephson junctions

Abstract: Eutectic Sr 2 RuO 4 -Ru samples with μm-sized Ru-metal inclusions support inhomogeneous superconductivity above the bulk transition of Sr 2 RuO 4 in the so-called 3-Kelvin phase. In Pb/Ru/Sr 2 RuO 4 Josephson junctions as realized by Maeno et al., a Pb film is indirectly coupled to the superconductor Sr 2 RuO 4 mediated by the proximity-induced superconducting Ru inclusions, yielding an extended Josephson contact through the interface between Ru and Sr 2 RuO 4 . Motivated by this experimental setup, we formula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The experimental observation of the anomalous temperature dependence of the critical current in the Pb-Ru-SRO Josephson junction reflects this modification, demonstrating that the Josephson current is limited by distinct mechanisms in phases with N = 0 (A-and A ′ -phases) and with N = ±1 (B-phase) 30 . The complete description of the temperature dependence of the Josephson current requires the discussion of the third spatial dimension of the device, which we avoid in this paper.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…The experimental observation of the anomalous temperature dependence of the critical current in the Pb-Ru-SRO Josephson junction reflects this modification, demonstrating that the Josephson current is limited by distinct mechanisms in phases with N = 0 (A-and A ′ -phases) and with N = ±1 (B-phase) 30 . The complete description of the temperature dependence of the Josephson current requires the discussion of the third spatial dimension of the device, which we avoid in this paper.…”
mentioning
confidence: 74%
“…Upon lowering the temperature further, I c quickly recovers. It is worth noting here, that the observation of a non-vanishing Josephson effect above T c,SRO demonstrates the presence of the 3K phase at the interface.It has been suggested that the anomalous temperature originates from a change of the limiting of the Josephson current between SRO and Ru (with proximityinduced s-wave pairing) 11,12,30 . While for the temperatures above T c,SRO the Josephson coupling could be as essentially uniform, below T c,SRO the chiral nature of the bulk superconducting state in SRO would yield a frustrated Josephson coupling with a considerably lower critical temperature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Etter et al 38 , proposed that transport properties of topological junctions based on the eutectic SRO-Ru system depend strongly on phase winding. They found that in the 3-K phase the phase winding is zero and junction exhibits ordinary or unfrustrated behaviour.…”
Section: Discussionmentioning
confidence: 99%